2011
DOI: 10.1021/ja108571a
|View full text |Cite
|
Sign up to set email alerts
|

Guanine-Rich RNAs and DNAs That Bind Heme Robustly Catalyze Oxygen Transfer Reactions

Abstract: Diverse guanine-rich RNAs and DNAs that fold to form guanine quadruplexes are known to form tight complexes with Fe(III) heme. We show here that a wide variety of such complexes robustly catalyze two-electron oxidations, transferring oxygen from hydrogen peroxide to thioanisole, indole, and styrene substrates. Use of (18)O-labeled hydrogen peroxide reveals the source of the oxygen transferred to form thioanisole sulfoxide and styrene oxide to be the activated ferryl moiety within these systems. Hammett analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
117
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(121 citation statements)
references
References 59 publications
4
117
0
Order By: Relevance
“…These systems pave the way to use the DNAzyme as a NAD + regeneration cycle for biocatalytic transformations and to implement the hemin/G-quadruplex as a catalyst for other chemical processes. Our systems complement the recently reported studies by Sen and co-workers [20] that demonstrated that hemin linked to G-rich RNAs and DNAs catalyze oxygen transfer reactions. All these novel biocatalytic functions of hemin/G-quadruplex suggest that further new processes might be catalyzed by this nanostructure.…”
supporting
confidence: 80%
“…These systems pave the way to use the DNAzyme as a NAD + regeneration cycle for biocatalytic transformations and to implement the hemin/G-quadruplex as a catalyst for other chemical processes. Our systems complement the recently reported studies by Sen and co-workers [20] that demonstrated that hemin linked to G-rich RNAs and DNAs catalyze oxygen transfer reactions. All these novel biocatalytic functions of hemin/G-quadruplex suggest that further new processes might be catalyzed by this nanostructure.…”
supporting
confidence: 80%
“…[43] Although the performance of a correlation of the kinetic data with either s or s + values has been proposed to support either a one step, concerted oxygen transfer or a two step, electron-transfer mechanism, caution has been suggested against using this kind of evidence as definitive proof of reaction mechanism. [44] As shown in Table 2, the rate constants for gas-phase sulfoxidation decline from thioanisoles to dimethylsulfide, a trend similarly found in solution and considered to demonstrate a single ET process. [45] Recent theoretical calculations revealed that Cpd I models with thiolate or imidazole proximal ligands react with dimethylsulfide via a concerted, single-step OAT, with a ligand-dependent spin-state selectivity.…”
mentioning
confidence: 66%
“…1317 Poon et al 18 also demonstrated that heme(Fe 3+ ) bound to the G-quartet of G-quadruplex DNAs and RNAs exhibits catalytic activity in oxygen transfer reactions. These findings have paved the way for exploring biological versatility of heme (Fe 3+ ) as prosthetic groups of DNAzymes and RNAzymes.…”
mentioning
confidence: 99%